KINERJA GURU SERTIFIKASI PADA MADRASAH ALIYAH SWASTA (MAS) PLUS PADANG GANTING KABUPATEN TANAH DATAR - Syafriadi M (IAIN Batusangkar, 2016)
: In this case study of qualitative approach the researcher analyzed the performance of civil servant and non civil servant teachers after certification. This research was conducted in Private Islamic High School (MAS) Plus Padang Ganting Tanah Datar. This research revealed that the civil servant teachers were better than non-civil servant teachers. Some of non civil servant teachers did not make lesson plan, did not make remedial program and an enriching program.Keywords: Teachers’ Performance, Private Islamic High School Plus Padang Ganting, Teachers’ Certification